(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The objective of this study was to compare the peculiarities in the mobilization of cardiovascular function at the onset of an exercise test in dependence on age and the type of adaptation to physical loads. The study’s participants were boys of 11, 12, 13 and 14 years old and adults, i. e. 17 voluntary students who were not engaged in sports training and well- trained athletes (all participants were members of various national teams), i. e. 23 athletes in the endurance group, 19 — in the sprint group and 21 — in the combative sports group (box, judo and wrestling). The subjects underwent: 1) Roufier’s test (30 squats per 45 seconds); 2) a 30-second duration maximal vertical jump test. A computerized electrocardiogram (ECG) system “Kaunas-Load” was employed for the 12-lead ECG recording and analysis during the performance of workloads. A computerized program allowed to measure the ratio of JT and RR intervals (JT / RR) and the velocity of adaptation of cardiovascular system to exercise, i.e. the index of velocity of adaptation (V Ad ), by calculation the difference between the relative changes of JT and RR intervals as a difference: V Ad . = (Jt i / JT 0 ) 100% – (Rr i / RR 0 ) 100%. The results obtained during the study allowed to conclude that faster adaptation at the onset of the exercise is rather characteristic for younger persons but the type of the exercise performed during the long term training process plays a significant role in the developing and improving the velocity of adaptation of cardiovascular system. A faster adaptation at the onset of the exercise is a more characteristic feature for the trained athletes in sprint events and combative sports than the representatives of the endurance group or non-athletes. One of the effects of long term adaptation to exercise is a smaller mobilization of cardiovascular system at the onset of the dosed aerobic and all-out anaerobic exercise and the endurance exercise has the most influence on it. Keywords: cardiovascular system, adaptation, exercise test.